Understanding Advertiser’s Intention: The Analysis of Presupposition Triggers in Advertisement - Nur Ijabah; Ade Windiana Argina (Acitya: Journal of Teaching and Education, 2022)
An advertisement is media that is used by a producer or company to reach their goal of selling the product as much as possible. Through language used in an advertisement, the advertiser tries to manipulate the audience’s minds to buy a particular product or service. One of the strategies to reach their goal is by employing presupposition in the advertisement. The presupposition is claimed to be able to give persuade potential consumers as well as to make the advertisement economic, as the information is concisely presented. This study aimed to investigate kinds of presupposition triggers employed in cosmetic advertisement namely SK-II. This study chose five videos of SK-II advertisement as the data. Then the videos were transcribed and selected the potential presupposition. Through analyzing presupposition triggers with the framework proposed by Levinson, it is hoped that this study will uncover the message employed in the advertisement, and help the reader understand the intention behind the language used in advertising so that they would be a wise consumer in deciding what products should be bought. Keywords: Presupposition triggers, advertisement, persuasive function